2015
DOI: 10.1007/s10973-015-4914-4
|View full text |Cite
|
Sign up to set email alerts
|

Combustion behaviors of cotton fabrics treated by a novel nitrogen- and phosphorus-containing polysiloxane flame retardant

Abstract: A novel flame-retardant agent, nitrogenand phosphorus-containing polysiloxane [(IB-co-N-MDPA)PDMS] was synthesized, and it was employed on cotton fabrics. Cone calorimeter testing showed that the treated cotton fabric with (IB-co-N-MDPA)PDMS became less flammable with longer time to ignition and lower value of HRR, THR, EHC and mass loss. Thermogravimetric analysis demonstrated that (IB-co-N-MDPA)PDMS improved the thermal and thermo-oxidative stability of cotton fabric with fewer flammable volatiles, and more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Partially studied [42][43][44][45][46][47][48][49] Nylon fabrics The nylon fabrics were dip-treated in a solution containing FR and crosslinker. MCC analyses showed a decrease of HRR, THR and HRC.…”
Section: Cottonmentioning
confidence: 99%
“…Partially studied [42][43][44][45][46][47][48][49] Nylon fabrics The nylon fabrics were dip-treated in a solution containing FR and crosslinker. MCC analyses showed a decrease of HRR, THR and HRC.…”
Section: Cottonmentioning
confidence: 99%
“…It was observed that the after flame time and damaged length of samples showed no obvious fluctuations within 10 washing cycles, meaning that washing treatment within 10 cycles had little effect on flame‐retardant of the cotton fabric. This result indicated that the polysiloxane coating seemed to be relatively stable and had a good adhesion due to the formation of covalent bonds between the coating and the cotton fiber . Additionally, the flame‐retardant properties showed a satisfying sustainability.…”
Section: Resultsmentioning
confidence: 88%
“…In order to further improve the flame retardant efficiency, some people also introduced phosphorus and nitrogen into organosilicon compounds [4,21], which constitutes a synergistic flame retardant system [22,23,24,25]. It is worth noting that almost no one will consider combining the flame retardancy and water repellency of polysiloxanes and applying them to cotton fabrics [26]. Therefore, the development of a multifunctional silicone-based auxiliaries for cotton fabrics has become a meaningful research work.…”
Section: Introductionmentioning
confidence: 99%